In vitro modelling of cellular haemozoin and inhibition by β-haematin inhibitors and their derivatives - Openshaw, Roxanne (University of Cape Town, 2021)
The discovery of new β-haematin inhibitors has become one focus for researches in response to the resistance of P. falciparum malaria parasites that emerged towards well-known antimalarials. While hundreds of new β-haematin inhibitors have been discovered using detergent mediated high-throughput screening methods, a crucial aspect is understanding exactly how these β-haematin inhibitors behave in the malaria parasite and inhibit the formation of haemozoin. What is known, is that well-known β-haematin inhibitors like chloroquine cause increased amounts of exchangeable haem in the parasite digestive vacuole and form a Fe(III)PPIX-inhibitor complex by accumulating at high concentrations which consequently inhibits parasite growth. Another important focus is on understanding the digestion of haemoglobin and its role in haemozoin formation. This research investigates the in vitro modelling of cellular haemozoin and inhibition by various β-haematin inhibitors across different scaffolds and the role of haemoglobin degradation in P. falciparum malaria parasites. The investigated β-haematin inhibitors resulted in micromolar IC50 (NF54) values and decreased parasite growth with increases in concentration. Using a pyridine-based parasite haem fractionation plate method, these β-haematin inhibitors were shown to target haemozoin formation by causing increased amounts of exchangeable haem that corresponded to decreasing amounts of haemozoin in chloroquine-sensitive parasites. The amounts of exchangeable haem were shown to be inversely proportional to the percentage of parasite growth in the presence of these β-haematin inhibitors. It was apparent that there was a tendency for parasite growth inhibition activity to decrease as the amount of exchangeable haem present in chloroquine sensitive parasites increased, although, the trend was not statistically significant. Moreover, it was observed that experimental cellular accumulation ratio values were low in comparison to chloroquine and amodiaquine. Based on the experimental cellular accumulation ratio values, it was deduced that the accumulation of these β-haematin inhibitors was not primarily due to pH trapping and more complex than previously proposed. Further investigations into the exchangeable haem amounts as a function of intracellular test compound amounts at the IC50 values of these β-haematin inhibitors highlighted that there was an apparent 1:1 relationship with the amount of intracellular exchangeable haem, indicative of complex formation. Transmission electron microscopy images were obtained for untreated parasites that showed intact parasites inside red blood cells with clearly visible haemozoin crystals dispersed throughout the parasite digestive vacuole, whilst, treated parasites showed less defined haemozoin crystals as a result of inhibition. Moreover, electron energy-loss spectroscopy revealed that untreated parasites exhibited a strong iron signal which was associated with haemozoin in the parasite digestive vacuole with a weaker signal attributed to the red blood cell cytoplasm. Similarly, a strong iron signal was shown in the digestive vacuole of treated parasites which was associated with less defined haemozoin crystals. A halo around these haemozoin crystals was observed and was suggested to be indicative of the build-up of exchangeable haem. Additionally, a strong bromine signal attributed to a bromine-containing β-haematin inhibitor, test compound 1, was also observed in the same region as the haemozoin crystals. Overlaid signal distribution maps for iron and bromine showed direct evidence of Fe(III)PPIX and test compound 1, suggesting complexation. High-quality Raman spectra were obtained for the Fe(III)PPIX species in red blood cells, chloroquine sensitive parasites and synthetically prepared samples for the Fe(III)PPIX porphyrin dominated spectral region of 1700-500 cm-1 at an excitation wavelength of 532 nm. From the spectra, a putative Fe(III)PPIX-test compound 1 complex was identified and shown to be similar to the synthetically prepared counterpart, haematin-test compound 1 mixture. It was highlighted that a unique peak at 1080 cm-1 indicated π- π interactions between the pyrrole-imidazole ring and thus confirming that the formation of this putative Fe(III)PPIX-inhibitor complex occurs. The confocal Raman true mapping technique proved to be efficient and reliable for imaging the signal distribution of haemozoin at the Raman peak of 754 cm-1 and 1080 cm-1 for the Fe(III)PPIX-test compound 1 complex which co-localized in the digestive vacuole of chloroquine sensitive parasites. Moreover, oxy- and deoxy-haemoglobin was observed to be localized to the red blood cell, where, deoxy-haemoglobin was located on the outer parts of the parasite. Principle component analysis, based on the Raman peak positions, exhibited significant differences in the spectra for Fe(III)PPIX species in red blood cells, chloroquine sensitive parasites and synthetic samples where clusters were observed to separate mainly along principle component 1. These data proved that the spectra of the Fe(III)PPIX-test compound 1 complex was the same as its synthetically prepared counterpart but different from the remaining Fe(III)PPIX species. In comparison to the Fe(III)PPIX-test compound 1 complex, the cluster separations were observed to be significant, where, no significant separation was observed for the Fe(III)PPIX-test compound 1 complex and the haematin-test compound 1 mixture. Based on this, it was evident that a Fe(III)PPIX-test compound 1 complex existed in the digestive vacuole of treated chloroquine sensitive parasites. To fully understand the inhibition of haemozoin, the development of a haem pathway model is necessary, but, requires certain prerequisites. Bioinformatics data from PAXdb and ExPASy revealed that chloroquine resistance (Dd2) parasites, containing 1337 previously identified proteins with an average abundance-weighted molecular weight of 40,483 ± 77 g/mol. With this, the protein mass per cell for red blood cells, chloroquine-sensitive and - resistant parasites were consistent across three protein quantification methods was measured and revealed that chloroquine resistant parasites had a significantly higher protein mass per cell than chloroquine sensitive parasites and in turn a higher total number of protein molecules per cell. Aspartic proteases are 4-fold higher in concentration than cysteine proteases with histo-aspartic protease having the highest concentration in chloroquine resistant parasites. Along with these data, a time point quantification for chloroquine sensitive parasites throughout the blood-stage showed that the amount of haemoglobin decreased in a sigmoidal manner and corresponded to a linear increase in the amount of haemozoin and relatively constant exchangeable haem amount. This was consistent with Giemsa smears that showed that for early time points, large initial decreases in the amount of haemoglobin were observed between the early trophozoite to late trophozoite stage.